1999
DOI: 10.1074/jbc.274.34.24054
|View full text |Cite
|
Sign up to set email alerts
|

Tubulin Folding Cofactors as GTPase-activating Proteins

Abstract: In vivo, many proteins must interact with molecular chaperones to attain their native conformation. In the case of tubulin, newly synthesized ␣-and ␤-subunits are partially folded by cytosolic chaperonin, a double-toroidal ATPase with homologs in all kingdoms of life and in most cellular compartments. ␣-and ␤-tubulin folding intermediates are then brought together by tubulin-specific chaperone proteins (named cofactors A-E) in a cofactor-containing supercomplex with GTPase activity. Here we show that tubulin s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
62
0
1

Year Published

2001
2001
2010
2010

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 110 publications
(67 citation statements)
references
References 42 publications
4
62
0
1
Order By: Relevance
“…Affinity-purified antibodies yielded similar results, with a decrease in nonspecific binding and specific antibody titer so that there was substantially reduced CoD signal intensity (data not shown). Fractionation of HeLa cell lysates by centrifugation at 100,000 ϫ g revealed that an estimated 90% or more of the protein fractionates in the S100 (data not shown), suggesting that the vast majority of CoD is cytosolic, as expected from the fact that CoD has twice been purified from cytosol (1,21,27). Indirect immunofluorescence of cultured mammalian cells revealed that CoD is also present at centrosomes, as seen by its co-localization with ␥-tubulin in both interphase and mitotic HeLa cells (Fig.…”
Section: Resultsmentioning
confidence: 94%
“…Affinity-purified antibodies yielded similar results, with a decrease in nonspecific binding and specific antibody titer so that there was substantially reduced CoD signal intensity (data not shown). Fractionation of HeLa cell lysates by centrifugation at 100,000 ϫ g revealed that an estimated 90% or more of the protein fractionates in the S100 (data not shown), suggesting that the vast majority of CoD is cytosolic, as expected from the fact that CoD has twice been purified from cytosol (1,21,27). Indirect immunofluorescence of cultured mammalian cells revealed that CoD is also present at centrosomes, as seen by its co-localization with ␥-tubulin in both interphase and mitotic HeLa cells (Fig.…”
Section: Resultsmentioning
confidence: 94%
“…1 legend). Release of radiolabeled inorganic phosphate was measured at 1 min intervals as described (10).…”
Section: Methodsmentioning
confidence: 99%
“…Each step in this pathway has been deduced from in vitro reconstitution experiments using purified components (7)(8)(9). The pathway hinges on the formation of a supercomplex containing ␣Ϫ and ␤-tubulin and cofactors C, D, and E. The hydrolysis of GTP by tubulin, stimulated by cofactors C and D, is part of the heterodimer assembly reaction; the stimulated hydrolysis of GTP by ␤-tubulin acts as a switch for the release from the supercomplex of native, newly made tubulin heterodimers (10). Cofactor C and D in combination have also been shown to be a GTPase activator (GAP) for native tubulin; cofactor E enhances this tubulin-GAP activity (10).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The biological significance of this process lies in the fact that the ability of ␤-tubulin to hydrolyze GTP is an essential property for the proper functioning of microtubule dynamics. The same reaction also serves to regulate microtubule dynamics by modulating the availability of GTP-bound heterodimers (14,15). Direct, biochemical evidence for a role of Arl2 in the complex process of the regulation of the action of one of these cofactors, cofactor D, was provided by Bhamidipati et al (16).…”
mentioning
confidence: 99%